Tasawuf Nusantara: Wuṣūl Perspektif Mbah Munshorif Dalam Al-Bidayat Majallatun Nihayat - M. Alan Al Farisi (Ma'had Aly Idrisiyyah, 2024)
Abstract This research is motivated by the oddity of Mbah Munshorif and his book. Mbah Munshorif is not an educated person but has an extraordinary book containing Sufism lessons, one of which explains about wuṣūl to Allah. To find out the figure of Mbah Munshorif and his concept of wuṣūl to Allah, the author then conducted a research with the title